Description of Incidence Dysmenorrhea in Relation to Physical Activity, Fast Food, and Tobacco Smoke Exposure Among Jakarta Female Students - Sukmayanti, Zanastia; violita, Eugienia; Amelia, Kurnia; Putri, Aulia Maharani; Putri, Wirda Cahya; Nisa, Hoirun (Journal of Religion and Public Health, 2025)
Dysmenorrhea is pain experienced during menstruation and can interfere with daily activities. A person's lifestyle such as physical activity and the habit of consuming fast food are factors that can affect the occurrence of dysmenorrhea. This study aims to determine the incidence of dysmenorrhea with physical activity, fast food consumption, and family smoking status in Public Health Students of UIN Jakarta. This study is a cross-sectional descriptive study with a sample of 212 female students. The prevalence of dysmenorrhea among Public Health students of UIN Syarif Hidayatullah Jakarta was 189 respondents (89.2%) out of 212 respondents. The level of dysmenorrhea suffered by many respondents was mild dysmenorrhea as many as 127 (59.9%). College students have a poor frequency of physical activity as many as 151 respondents (71.2%). College students have a habit of eating fast food as many as 203 respondents (95.8%). There were 104 family members who smoked (49.1%). Students who experience dysmenorrhea by consuming fast food were 181 respondents (89.2%), students who experience dysmenorrhea with poor physical activity were 134 respondents (88.7%) and students who experience dysmenorrhea with exposure to family members who smoke were 95 respondents (91.3%). Suggestions for female students to reduce the incidence of dysmenorrhea are, avoid fast food, increase real food consumption, exercise regularly to reduce menstrual pain and avoid cigarette smoke from various sources. Suggestions for further researchers to further explore other factors that can affect the incidence of dysmenorrhea.